Vegetazione e ambiente delle Marche e relativi problemi di salvaguardia - Pedrotti, Franco (Giornale botanico italiano, 1976)
Abstract Vegetation and environment in the Marche and related problems of protection. ? The « Marche » region is situated in central Italy and corresponds with the natural region east of the Appennine ridge and spreading as far as the coast which is washed by the Adriatic Sea. As to the climate, we may distinguish a coastal strip with Mesomediterranean climate with dry season, corresponding to the distribution area of Quercus ilex; a hilly strip with Submediterranean climate, corresponding to the distribution area of Quercus pubescens; a mountain strip with temperate axeric climate with sub-dry period, corresponding to the distribution area of Fagus silvatica and finally a high mountain strip with cold axeric climate, corresponding to altitude pastures. The Marche vegetation is shown in the vegetation map of Fabriano sheet (scale 1:50,000) plotted according Ozenda's vegetational series. The following vegetation series have been plotted: submediterranean series of Quercus ilex; series of thermophilic oak wood with priority of Quercus pubescens or Quercus cerris; series of Ostrya carpinifolia; series of Quercus petraea and series of Fagus silvatica. As far as the problems to safegard environment are concerned, a plan is given providing for the institution of 4 complete nature reserves, 34 nature reserves, and 9 regional nature parks among which those of Monte Conero, of Monti Sibillini and Monti della Laga.
doi: 10.1080/11263507609426403
Keywords: Marche (PG); vegetation series